Diffuse Alveolar Hemorrhage: A Rare Life-Threatening Condition in Systemic Lupus Erythematosus - Ravi Paul Singh Virdi; Adeel Bashir; Ghulamullah Shahzad; Javed Iqbal; Jose O. Mejia (Case Reports in Pulmonology)
Diffuse alveolar hemorrhage (DAH) is a rare life-threatening complication in systemic lupus erythematosus (SLE) associated with high mortality rates. DAH is more common in women, and mean age of onset is around 30 years. It mostly occurs in patients with established diagnosis of SLE but can be the initial presentation of lupus in approximately 20%. DAH should be suspected in lupus patient presenting with new pulmonary infiltrates, decline in hemoglobin, hemoptysis, dyspnea, hypoxemia, and increase in carbon monoxide diffusion capacity. Radiographic evidence of bilateral pulmonary alveolar infiltrates that are usually perihilar or basilar with sparing of apices is seen. DAH can often mimic clinically and radiologically severe pneumonia or ARDS. Treatment includes high-dose corticosteroids, cyclophosphamide, and plasmapheresis. We report a case of diffuse alveolar hemorrhage complicating SLE flare-up in a male patient.